Belive in ALLAH - AL-MARWANI, AMATULLAH (GOODWORD BOOKS New Dehli, 2022)
"Believe in Allah" is a thought-provoking exploration of faith and spirituality, emphasizing the importance of belief in Allah as a central tenet of Islam. The book delves into the concepts of trust, submission, and devotion, illustrating how a strong belief in Allah can guide individuals through life's challenges and uncertainties. It incorporates teachings from the Quran and Hadith, offering insights into how faith shapes one's character, values, and relationships with others. The work aims to inspire readers to deepen their understanding of their faith, fostering a sense of purpose and connection to the divine.